2019
DOI: 10.1080/14797585.2019.1665894
|View full text |Cite
|
Sign up to set email alerts
|

Assembling the refugee anthology

Abstract: There has been a sudden proliferation of short story anthologies published in response to the refugee 'crisis' of 2015 and the US travel ban of 2017. This article focuses on two of these collections (The Displaced and Banthology, both 2018) in order to ask: what makes an anthology better equipped than a single authored piece of writing to respond to contemporary themes such as migration and displacement? The answer might lie in their heterogeneous form, which allows anthologies to be assembled and reassembled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In English-medium writing on refugee experience, for instance, Anna Bernard (2020) has recently suggested that three genres dominate-poetry, graphic narrative, and verbatim theatre-because of their modes of production and because of the kinds of engagement they ask of their audience. To these we might add the proliferation of short story anthologies published in direct response to the refugee 'crisis' of 2015 in Europe and the US travel ban of 2017 (Bond, 2019). These are all literary forms (among others) which, therefore, a critical literary multilingualism studies needs to take into its purview in order to be able to ask how they figure (or don't) the linguistic unmooredness which is attendant on becoming a refugee, and which is therefore a predominant multilingualism of the world today.…”
Section: Journal Of Literarymentioning
confidence: 99%
“…In English-medium writing on refugee experience, for instance, Anna Bernard (2020) has recently suggested that three genres dominate-poetry, graphic narrative, and verbatim theatre-because of their modes of production and because of the kinds of engagement they ask of their audience. To these we might add the proliferation of short story anthologies published in direct response to the refugee 'crisis' of 2015 in Europe and the US travel ban of 2017 (Bond, 2019). These are all literary forms (among others) which, therefore, a critical literary multilingualism studies needs to take into its purview in order to be able to ask how they figure (or don't) the linguistic unmooredness which is attendant on becoming a refugee, and which is therefore a predominant multilingualism of the world today.…”
Section: Journal Of Literarymentioning
confidence: 99%
“…8 The anthologies vary in their modes of composition, from ones that comprise works written specifically for the collection to ones that offer a selection of already published works that span different historical periods and locations. Bond (2019) European country] is in stark contrast with the daily images of the clandestine emigrants who risk their lives in the boats of fortune that have sadly transformed the Mediterranean into a giant cemetery for African migrants" (Sarr, 2019: 65). 12 For a discussion that engages Italy, past and present, see Wallace (2015-16).…”
Section: From Superman To 1938: Literary Collections As Dialoguesmentioning
confidence: 99%